The "enemy within" the post-Vatican II Roman Catholic Church - Duncan, Graham (HTS teologiese studies, 2013)
The Second Vatican Council (1962–1965) is regarded as one of the most significant processes in the ecumenical church history of the 20th century. At that time, a younger generation of Roman Catholic theologians began to make their mark in the church and within the ecumenical theological scene. Their work provided an ecumenical bridge between the Reforming and the Roman Catholic ecclesiastical traditions, notwithstanding the subsequent negative response of the Roman church hierarchy. Despite important advances, recent pontificates significantly altered the theological landscape and undermined much of the enthusiasm and commitment to unity. Roman Catholic theological dissent provided common ground for theological reflection. Those regarded as the ‘enemy within’ have become respected colleagues in the search for truth in global ecclesiastical perspective. This article will use the distinction between the history and the narratives of Vatican II.